Analysis of the flow characteristic inside a heated and unheated horizontal rifled tube - Soo, Poey Lam (2012)
Rifled tube which is one of the rough surface tube has been getting attention from researchers due to its ability to enhance the heat transfer. Previous researches on rifled tube has been done through experimental work. Therefore, numerical analysis by using commercial Computational Fluid Dynamics (CFD), Fluent® has been carried out to investigate the flow characteristic of the single phase flow in 2 meters long of horizontally rifled tube and smooth tube under heating condition and without heating condition at the outer wall. The rifled tube or also known as spiral internally ribbed tube that is used in this investigation has an outside diameter 45.0 mm and inside equivalent diameter of 33.1 mm while the smooth tube has an outside diameter 45 mm and inside diameter 34.1 mm. The working fluid that is used in this investigation is water. In this numerical analysis, realizable k-epsilon model has been chosen to solve the fully developed turbulence flow in the rifled tube and smooth tube. The result of the numerical analysis showed that there was swirling effect at the near-wall-region for both the case of the rifled tube under heating condition and without heating condition at the wall. The flow characteristic of the rifled tube in terms of pressure drop when there is no heat flux condition at the outer wall shows that the pressure drop in rifled tube is 1.69 – 1.77 folds than in the smooth tube. Meanwhile, when there is heating at the wall of the tubes, the pressure drop and heat transfer coefficient in rifled tube are about 1.67-2.0 times and 0.97-1.27 times respectively, than in smooth tube. The high pressure drop and Nusselt number in rifled tube is due to the helical rib in the rifled tube which not only has disturbed the flow but also causes swirling effect near the wall. As a result, the heat transfers from the wall to the flow near the wall region is enhanced. The present study also has proved that although the rifled tube produces high pressure drop but it is good in heat transfer enhancement through the ratio of heat flux to the pumping power.